2002
DOI: 10.1161/01.res.0000038961.53759.3c
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Coronary Vessel System

Abstract: Abstract-Formation of the coronary vessels is a fundamental event in heart development. Congenital abnormalities in the coronary system can have major deleterious effects on heart function. It is also possible that subtle variation in the patterning of coronary vessels has significant but uncharacterized effects on myocardial structure and function. In addition, generation of the coronary vascular system represents a complex system for analysis of regulation of cell fate determination, cell and epithelial migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
173
0
6

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 203 publications
(185 citation statements)
references
References 53 publications
6
173
0
6
Order By: Relevance
“…The genesis of coronary vessels is an intricate process integrally associated with the development of the epicardium, a structure arising from the proepicardium, a derivative of the developing liver (Bernanke and Velkey, 2002;Reese et al, 2002). Our finding of a lack of coronary vessels appears to arise from problems with the proper formation and maintenance of the epicardium, similar to the ␣4 integrin (Yang et al, 1995), VCAM (Kwee et al, 1995), and WT1 (Moore et al, 1999) null mice.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The genesis of coronary vessels is an intricate process integrally associated with the development of the epicardium, a structure arising from the proepicardium, a derivative of the developing liver (Bernanke and Velkey, 2002;Reese et al, 2002). Our finding of a lack of coronary vessels appears to arise from problems with the proper formation and maintenance of the epicardium, similar to the ␣4 integrin (Yang et al, 1995), VCAM (Kwee et al, 1995), and WT1 (Moore et al, 1999) null mice.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of coronary vasculature may reflect one of two things: (1) a defect with the epithelial-to-mesenchymal transition from the epicardium (Tevosian et al, 2000); or (2) a defect in the epicardium itself (Moore et al, 1999;Bernanke and Velkey, 2002;Morabito et al, 2002;Reese et al, 2002). Analysis of tissues for the presence or absence of the epicardium using the marker, Wilm's tumour 1 (WT1; Moore et al, 1999;Tevosian et al, 2000;Wagner et al, 2002) revealed that, in animals with no coronary vessels, the epicardium was either absent or defective.…”
Section: Double Trangenic-ang1 Mice Have No Coronary Vesselsmentioning
confidence: 99%
See 3 more Smart Citations